Afterlives of Slavery: Afrofuturism and Afropessimism as Parallax Views - Hart, William David (Black theology, 2021)
If stars appear to change position, to be displaced when viewed from different point in the earth's orbit, then by analogy we might say that Afrofuturism and Afropessimism are parallax angles on the afterlife of slavery. Afrofuturism and Afropessimism inhabit forms of imaginative spacetime that are both congruent and incongruent. I will call the triangular relations among the afterlife of slavery, Afrofuturism, and Afropessimism, a “black mood.” While this mood certainly has psychological meaning for individuals, I primarily point toward a sociological phenomenon that shapes the collective mood long term. This black mood is an intellectual disposition with emotional resonance. It produces both empowering joyful affects and disempowering sad affects. Though it is hardly the only black mood, this one is influential in sectors of the Blackamerican intelligentsia both within and beyond the academy. In this article, I explore a few points of contact among Afrofuturism, Afropessimism, and black religion.